Host and Species-Specificities of Pattern Recognition Receptors Upon Infection With Leptospira interrogans - Delphine Bonhomme; Catherine Werts (Frontiers in Cellular and Infection Microbiology, 2022)
Leptospirosis is a zoonotic infectious disease affecting all vertebrates. It is caused by species of the genus Leptospira, among which are the highly pathogenic L. interrogans. Different mammals can be either resistant or susceptible to the disease which can present a large variety of symptoms. Humans are mostly asymptomatic after infection but can have in some cases symptoms varying from a flu-like syndrome to more severe forms such as Weil’s disease, potentially leading to multiorgan failure and death. Similarly, cattle, pigs, and horses can suffer from acute forms of the disease, including morbidity, abortion, and uveitis. On the other hand, mice and rats are resistant to leptospirosis despite chronical colonization of the kidneys, excreting leptospires in urine and contributing to the transmission of the bacteria. To this date, the immune mechanisms that determine the severity of the infection and that confer susceptibility to leptospirosis remain enigmatic. To our interest, differential immune sensing of leptospires through the activation of or escape from pattern recognition receptors (PRRs) by microbe-associated molecular patterns (MAMPs) has recently been described. In this review, we will summarize these findings that suggest that in various hosts, leptospires differentially escape recognition by some Toll-like and NOD-like receptors, including TLR4, TLR5, and NOD1, although TLR2 and NLRP3 responses are conserved independently of the host. Overall, we hypothesize that these innate immune mechanisms could play a role in determining host susceptibility to leptospirosis and suggest a central, yet complex, role for TLR4.